Evolving Threats, Evolving Laws: Balancing Rights and Security in Indonesia's Terror Law and Counterterrorism Strategy - Hasibuan, Hoiruddin; Handoko, Waluyo; Sagor, Anwar Hossan (Universitas Islam Sultan Agung, 2022)
This research examines the legal approach to terrorism in Indonesia, focusing on the regulatory framework established by Government Regulation in Lieu of Law No. 1 and No. 2 of 2002, later amended into Law No. 15 of 2003. The background of the study involves a series of terrorism events, such as the Bali bombings in October 2002, prompting the government to respond with significant legal changes. The aim of this research is to analyze the impact and effectiveness of legal changes in addressing terrorism, considering both preventive and repressive aspects. The research method involves analyzing legal texts and related documents, utilizing a descriptive approach to understand the implementation of these laws. The problem formulations include evaluating the concepts of counter-radicalization and deradicalization as preventive strategies, as well as examining the sustainability of law enforcement efforts and terrorism financing. The research findings indicate that existing laws reflect the government's responsibility to protect citizens and secure the territory from cross-border terrorist threats. However, there are criticisms of the universal definition of terrorism and substantial weaknesses in the Terrorism Law, including aspects of criminal procedural law and human rights. In conclusion, there is a need for improvements in positive law, including the possibility of amending the Terrorism Law to ensure an effective response to evolving and complex terrorism threats.